Consumers' prestige-seeking behavior in premium food markets: Application of the theory of the leisure class. (January 2019) - Lee, Hojin; Jang, Yoon; Kim, Youngshin; Choi, Hyung-Min; Ham, Sunny
Highlights: This study attempted to investigate customers' value perceptions in the premium food markets. This study investigated the effect of value dimensions on consumer affective commitment toward premium food markets. This study investigated the effect of consumer affective commitment on behavioral intentions to premium food markets. Using a self-administered survey from premium food market customers, 247 valid responses were obtained for data analysis. This study was the first empirical investigation to apply the values of prestige to premium food markets. Abstract: Premium food markets have emerged as a new form of foodservice establishment. They feature a unique eating and shopping experience that offers a wide variety of high-quality food in a sophisticated environment with distinctive consumer services. Based on the theory of the leisure class, this study explored how consumers' prestige values influence their behavioral intentions, particularly their customer citizenship behavioral intention and revisit intentions, toward premium food markets. The study sample included customers who have shopped at premium food markets. Using a self-administered survey, 247 valid responses were obtained for analysis. The results showed the positive effects of prestige values on affective commitment and the positive influences of affective commitment on customer citizenship behavioral intention and revisit intention. This study significantly extends prestige-consumption knowledge in the foodservice and hospitality industries.